2018
DOI: 10.3319/tao.2018.02.23.02
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of diffusion coefficient of methane in water/brine under high pressure

Abstract: The diffusion coefficient of methane in water plays an important role in the formation and dissociation of methane hydrate. However, most of the previous studies on the diffusion coefficient of methane in brine are performed at room temperature and low pressures, which is quite different from the formation condition of methane hydrate. In this study, we measure the diffusion coefficient of methane in pure water and brine in capillary tube at 10.3 MPa and temperature ranging from 283.15 to 308.15 K. We use the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…The D 0-C1 range was determined by considering the variability in published values. For the low value, D 0-C1 was reduced by 8% compared to the base case to match the data from Chen et al (2018). For the high value, the D 0-C1 was increased by 20%, consistent with the results of Pokharel et al (2017).…”
Section: Sensitivity Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The D 0-C1 range was determined by considering the variability in published values. For the low value, D 0-C1 was reduced by 8% compared to the base case to match the data from Chen et al (2018). For the high value, the D 0-C1 was increased by 20%, consistent with the results of Pokharel et al (2017).…”
Section: Sensitivity Analysissupporting
confidence: 80%
“…Pressure dependence of diffusion coefficients is not implemented in PHREEQC. Chen et al (2018) found that the diffusion coefficient for methane was insensitive to pressures up to 100 atm. Therefore, it was assumed that pressure does not affect the D 0 of C 1 , C 2 , and C 3 .…”
Section: Diffusionmentioning
confidence: 99%
“…Fewer data are available for CO 2 in ethanol [35,10,11,36,37,29,38], cyclohexane [39], toluene [10,40,41], methanol [35,10,11,19,31,42], and acetone [10]. For CH 4 , diffusion coefficients have been investigated before in water [8,43,9,44,45,46,47,48,34].…”
Section: Introductionmentioning
confidence: 99%
“…Several measurement techniques have been applied including the Taylor dispersion technique, NMR, pressure-time measurements and also chromatographic analysis from a diffusion cell. The diffusion coefficients of methane in water have also been thoroughly investigated experimentally and mathematically using methods such as the capillary cell method, the diaphragm method, the inverted tube method, the modified barrier method and a simplified method where the capillary tube was used with in situ Raman spectroscopy [28][29][30][31][32][33][34][35][36][37]. Other studies on the diffusion of methane in liquid hydrocarbons have focused on heavy crude oils and bitumen [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%